2019
DOI: 10.1002/jcb.28664
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: High expression of TCF12 contributes to gastric cancer development via being target regulated by miR‐183 and activating PI3K/AKT pathway

Abstract: This study aimed to explore the role of transcription factor 12 (TCF12) in the process of gastric cancer (GC) and to elucidate its possible regulatory mechanism. The expression data of GC tissues and matched normal tissues were downloaded from The Cancer Genome Atlas (TCGA) database. Survival analysis for GC patients with different levels of TCF12 was performed by the Kaplan-Meier analysis. In addition, TCF12 was suppressed in human GC cell lines AGS and MKN-45, followed by detecting cell biological processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In hepatocellular carcinoma, overexpression of TCF12 in human HCC cells enhances cell proliferation, migration, and invasion (Yang et al, 2019). In gastric cancer, suppression of TCF12 inhibits proliferation of gastric cancer cells via regulation by miR‐183 (Wang, Gao, et al, 2019). In contrast, in prostate cancer, TCF12 suppresses the proliferation, invasion, and migration of prostate cancer cells (Q.…”
Section: Discussionmentioning
confidence: 99%
“…In hepatocellular carcinoma, overexpression of TCF12 in human HCC cells enhances cell proliferation, migration, and invasion (Yang et al, 2019). In gastric cancer, suppression of TCF12 inhibits proliferation of gastric cancer cells via regulation by miR‐183 (Wang, Gao, et al, 2019). In contrast, in prostate cancer, TCF12 suppresses the proliferation, invasion, and migration of prostate cancer cells (Q.…”
Section: Discussionmentioning
confidence: 99%
“…13 Increasing studies have shown that TCF12 acts as an oncogene/a tumor suppressor in a variety of human cancers. 14 For instance, TCF-12 is a potential molecular target that inhibits the invasion and metastasis of gallbladder cancer cells. 15 TCF12 is significantly elevated in cancer-related fibroblasts, causing extracellular matrix remodeling and triggering invasion and metastasis of breast cancer cells in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…RT-qPCR and western blot showed that Nur77 knock-out could effectively reduce the expression of CXCR4 and PI3K in U257 and U87 cells. CXCR4 is a key factor mediating PI3K activation [26], which is critical for the activation of the biologi-cal activity of tumour cells [27][28][29][30]. In this study, cellular immunofluorescence assay showed that Nur77 knock-out significantly reduces the nuclear entry of PI3K protein, which may be the main factor leading to the decrease in biological activity of U257 and U87 cells.…”
Section: Discussionmentioning
confidence: 58%